Technical and Vocational Education and Technology Transfer: Departments of Computer and Communications at the Public Authority for Applied Education and Training, PAAE&T, Kuwait, As A case Study - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
The transfer of technology plays a vital role in the advancement of a country, particularly in gulf states where the shortage of skilled and semi-skilled in visible in essential sectors on their economy (e.g., oil, health, water and electricity). The transfer of technology is considered a significant factor in the development, and is most effective and efficient. When it is absorbed in such a way as to provide a springboard for the move into the next stage of industrialization. The transfer of technology to Kuwait has brought with it enormous changes in terms of industrial development, lower the rate of youth unemployment, increase wages, and upgraded the standard of living. However, the success of technology transfer depends extensively on the contribution of the imported technology in building a sound indigenous scientific and technical infrastructure. In other word, the ability to transfer the know-how and know-why to indigenous manpower that are capable of managing, monitoring, maintaining, and adapting the imported technology to suit local environment. In this paper, I present some of the empirical results and observations which describe the interactions between the supplier of technology (Internet Works and Communications System) and the recipient of the technology (PAAE&T) in the field of technology transfer. In other word, whether the PAAE&T have taken the opportunity, while building its new headquarter, in the transfer of technology from the supplier of internet works and communications system to its academic staff in the various computer and communication academic departments at the PAAE&T colleges and institutions. The paper argues that, for effective and efficient transfer of technology, the recipient (PAAE&T) must ensure that the agreement with the supplier of Internet Works and Communications System must include calluses that would allow the PAAE&T academic staff in its various computer and communications academic departments in its various colleges and institutions to acquire the technology embedded in the agreement. The paper concludes that the transfer of technology and the building of a local scientific and technical infrastructure must be viewed by Kuwaiti decision-makers as a complementary to one another. Thus, reducing, to great extent, the level of dependence on expatriate, particularly in essential sector of the economy (e.g., oil, electricity and water, health).